Expert consensus on medical nutrition therapy for people with type 2 diabetes - Alejandro Marin Sánchez; Katherine Restrepo Erazo; Karen Palacios Bayona; Angelica Veloza Naranjo; Sandra Mora Thiriez; Lina M Valencia; Carlos O Mendivil (Revista Colombiana de Endocrinología, Diabetes y Metabolismo)
Context: Medical nutritional therapy is a cornerstone intervention for managing type 2 diabetes. However, despite existing clinical guidelines, robust evidence to support recommendations on many topics remains limited.